2022
DOI: 10.1021/acs.jchemed.2c00090
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Undergraduate Analytical Chemistry Curriculum

Abstract: This article reports the results of a curriculum survey of 322 analytical chemistry instructors (92% U.S.-based) conducted during Spring 2021. This snapshot of current course formats, topics, and pedagogical methods will be useful to both seasoned and novice teachers of analytical chemistry. The majority of respondents reported that their major requires two analytical chemistry courses, and 97% of respondents reported that at least one analytical course is required. Over 80% reported a required analytical lab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 37 publications
(73 reference statements)
0
49
0
Order By: Relevance
“…A recent survey of analytical chemistry instructors found that chromatographic theory, HPLC instrumentation, and GC instrumentation were rated as some of the most important topics in the curriculum (Fig. 1 ) [ 41 ]. In virtual learning environments, hybrid approaches that combine synchronous, real-time instruction with asynchronous, on-demand content access have been widely adopted [ 42 , 43 ].…”
Section: Content Delivery Approaches Utilizing Advanced Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent survey of analytical chemistry instructors found that chromatographic theory, HPLC instrumentation, and GC instrumentation were rated as some of the most important topics in the curriculum (Fig. 1 ) [ 41 ]. In virtual learning environments, hybrid approaches that combine synchronous, real-time instruction with asynchronous, on-demand content access have been widely adopted [ 42 , 43 ].…”
Section: Content Delivery Approaches Utilizing Advanced Technologymentioning
confidence: 99%
“…1 General results of survey of analytical chemistry instructors on topics covered in their courses organized by average rating of importance. Reprinted with permission from [ 41 ] (Copyright 2022 American Chemical Society)
Fig. 2 Primary user interface of the ‘Practical HPLC Simulator’ program.
…”
Section: Content Delivery Approaches Utilizing Advanced Technologymentioning
confidence: 99%
“…All areas of chemistry and other science and engineering disciplines highly rely on this branch of measurement science. Current undergraduate courses focus on lectures which provide depth on the core principles of conducting measurements (e.g., accuracy, precision, sample preparation, sampling, and validation) and the theory on how instruments or techniques work (e.g., titrimetric analysis, spectroscopy, electrochemistry, and chromatography). These lectures are contextualized through practical work, providing opportunities to understand instrumentation and enhance practical skills. ,, It is often practical skills that are essential to enhance the employability prospects of analytical chemistry graduates. , …”
mentioning
confidence: 99%
“…2 The analytical chemistry curriculum has been surveyed. 3 Efforts to understand the inorganic curriculum via a national survey have also been recently been reported. 4 Thus, while there has been some level of stability related to the chemistry content within subdisciplines, the very nature of chemistry and discoveries within the science have always encouraged creative thought about what students should learn in any given area of the field.…”
mentioning
confidence: 99%
“…Relatively recent efforts to characterize the “threads of the warp” include analysis of general chemistry content considering patterns in testing . The analytical chemistry curriculum has been surveyed . Efforts to understand the inorganic curriculum via a national survey have also been recently been reported .…”
mentioning
confidence: 99%